Work Accelerating Committees as a Means of Implementation of the Contractor's Expense in Public Works Contracts - Dr. Hanadi Fawzi Hussein, Dr. Waleed Khashan Zughair, (Opción, 1970)
The public enterprise contract plays a vital role in developing the service providing and investment situation in Iraq, in spite of this fact, unfortunately this role may be hindered if the projects, especially in its final stages, are impeded in all cases the contract ant fails to accomplish his obligation for one reason or another. Therefore there is an urgent need to overcome this impediment by forming ad hoc accelerating committees to complete the remained unfinished works of the project at the cost of the contract without entering into the costly and complicated procedure of the withdrawal of the project.